Contemporary authorship guidelines fail to recognize diverse contributions in conservation science research. Issue 2 (26th April 2021) - Cooke, Steven J.; Nguyen, Vivian M.; Young, Nathan; Reid, Andrea J.; Roche, Dominique G.; Bennett, Nathan J.; Rytwinski, Trina; Bennett, Joseph R.
Abstract: Authorship should acknowledge and reward those deserving of such credit. Moreover, being an author on a paper also means that one assumes ownership of the content. Journals are increasingly requiring author roles to be specified at time of submission using schemes such as the contributor roles taxonomy (CRediT) system, which relies on 14 different roles. Yet, there are many other aspects of research that are not adequately captured by the list of roles, particularly in applied environmental disciplines such as conservation science, environmental science and applied ecology. The growing recognition that authorship should reflect contributions that extend beyond the usual data collection, analysis and writing provides the ideal backdrop for rethinking contributions in conservation science. Here we propose a more inclusive approach to authorship that recognizes and values diverse contributions and contributors using an expanded list of CRediT roles. Abstract : Determining who is deserving of authorship is challenging. That is particularly salient in conservation science where contributions are diverse and may extend beyond data collection, analysis or writing. This image illustrates the interconnectedness of contributors and the challenges with determining who has earned authorship.